ANALISIS YURIDIS PERTIMBANGAN HAKIM TERHADAP PENJATUHAN PIDANA PEMBINAAN DALAM LKSA KASUS PEMBUNUHAN BEGAL OLEH SISWA SMA DI MALANG (STUDI PUTUSAN) - Cherry Angella Haryono (Fakultas Hukum Universitas Tarumanagara, 2021)
Unintentional homicide is a murder that is carried out unintentionally and is a form of crime whose consequences are not desired by the perpetrator, because of the negligence of the perpetrator from the act, a result is categorized as a criminal act. In this error, the perpetrator is not aware of his actions and has no intention to harm the victim, but due to his negligence and carelessness, his actions cause the loss of another person's life. Crime is an intentional act or negligence in violating the criminal law, the law determined in legislation and jurisprudence, carried out not for self-defense and without justification, and determined by the State as a serious crime (felony) or a minor crime (misdemeanor). Self-defense is an action in self-defense or self-defense is an act of self-defense, defending property or wealth from others that can harm physically. Article 49 paragraph (1) of the Criminal Code regulates the actions “emergency” defense (noodweer) for themselves and for others, decency, honor or property themselves or others, because an attack or threat of attack is very close. According to this article people World Health Organization do defense emergencies can not be punished. Factors That Makes Working Out Perpetrators of Criminal Punishment by Penal Code are: Ontoerekenings- vatbaarheid (an inability responsible), Overmacht (necessity) forced or emergency, Noodweer (urgent advocacy), Wettelijk voorschrift (command laws), bevel Ambtelijk (command term).